Is Religiosity An Important Factor In Influencing The Intention To Undertake Islamic Home Financing In The Klang Valley? - Syed Shah Alam; Janor, Hawati; Jano, Zanariah; Che Wel, Che Aniza; Nilufar Ahsan (IDOSI Publications, 2012)
The paper is intended to determine whether religiosity is an important factor in influencing the intention to undertake Islamic home financing in Malaysia. A consumer survey comprised a sample of 300 Muslim respondents from various range of age and income group resided mainly in Klang Valley areas. A conceptual framework is constructed based on Ajzen’s [15] Theory of Planned Behaviour (TPB) and research hypothesis are developed in order to focus attention on sets of factors that influences intention to use Islamic home financing in Malaysia. The findings indicated that religiosity had significant influences on the intention of Islamic home financing among Muslims in Klang Valley. In addition, this study also confirms that the TPB components namely attitude and perceived behavior are significant factors as well. Key words: Religiosity Islamic home financing Customer Islamic banking.